A crítica literária de Ana Cristina Cesar: verdade e máscara - Pontes, Brenda Maria Pereira de (2020)
The present work consists of the investigation of the critical production of the contemporary Brazilian poet, translator, and literary critic Ana Cristina Cesar, as of the problematic of the relation between fiction and reality, a theme frequently approached by the scholars who study her poetic writings, but not yet widely discussed in her critical texts. For that, we dedicate ourselves to the texts of Literatura não é documento (1980) and Escritos no Rio (1993), later published in Crítica e Tradução (2016), whose frequent objects of discussion are marginal poetry, autobiographical genres, the critical exercise itself and documentary cinema. In the aforementioned compilation, Cesar presents a questioning position on issues concerning the truth and the mask, reverberating the propositions of theorists with a structuralist and poststructuralist inclination, in addition to raising a proposal for aestheticizing reality in fictional works, which can be seen throughout her critical trajectory. As for the theoretical support of our research, we turn to the postulates of historiographic bias by Flora Süssekind (2004), Heloísa Buarque de Hollanda (2004), Ítalo Moriconi (2016), to approach the literature of the 1970s; Roland Barthes (2004), regarding critical discourse and authorship; Michel Foucault (2011), concerning the author function and the self-writing; and Michael Hamburger (2007), regarding the idea of a mask. Thus, taking into consideration what we have researched and discussed throughout this dissertation, we have concluded that the proposals of aestheticization and pretense are the main perspectives from which Cesar reflects about literature, which also reveals an independent attitude in her critical and theoretical positions, to the detriment of the inclinations of literary studies in force at the time in Rio de Janeiro.